Framework for assessing cable car construction investment projects: Examining investment projects in Taiwan - Hsin-Lung Liu; Wei-Ling Hsu (Advances in Mechanical Engineering, 2015)
The use of low-carbon evaluation indices for tourist attractions facilitates the promotion of low-carbon tourism. However, balancing tourism and environmental considerations has become critical to the development of the tourism market. Compared with road vehicles, cable cars are environmentally friendly, convenient, and economical. This study presents a framework for evaluating cable car development projects on the basis of the following aspects: (a) determining guidelines for cable car stations and route layouts, (b) establishing a logical framework for assessing the feasibility of cable car systems, (c) identifying station assessment items, and (d) evaluating the assessment items for potential routes by applying the analytic hierarchy process. These aspects can facilitate executing thorough and pragmatic assessments of cable car development projects.